Peranan Alat Bukti Tambahan: Studi Kasus Tindak Pidana Korupsi - Muh. Nasir; Bambang Nurdiantoro (Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This research aims to examine and analyze the additional proof role and the factors that influence it in eradicating the criminal act of corruption. This research uses empirical legal research methods. The primary data collection was carried out using a questionnaire, while the secondary data was collected using literature study techniques. The data obtained in this research is then quantified using a quantitative descriptive analysis model, then described using a frequency distribution table for answer research purposes. The results show that additional proof has a very large role in eradicating the criminal act of corruption. In this case, the scope of proof regulated in Law No. 8 of 1981 is still limited, while Article 26A of Law No. 20 of 2001 is quite broad. Furthermore, the factors of legal substance, legal structure, and legal culture also significantly affect the use of additional proof in eradicating the criminal act of corruption. Therefore, it is recommended that the House of Representatives amend Law No. 8 of 1981 regarding the additional proof. Furthermore, it is recommended that law enforcers pay attention to the details of the additional proof regulated in Article 26A of Law No. 20 of 2001 to maximize the eradication of the criminal act of corruption in Indonesia.